Association between serum free fatty acids and gestational diabetes mellitus - Li, Danyang; Du, Haoyi; Wu, Na (Frontiers in Endocrinology, 2024)
Background: Pregnant women with gestational diabetes mellitus (GDM) are at an increased risk of adverse pregnancy outcomes (APO). Early understanding of risk factors affecting these outcomes may facilitate preventive interventions for women at high risk. Blood samples from GDM and control pregnant women were collected for Free fatty acid (FFA) profiling to determine the relationship with the occurrence of APO in GDM pregnant women. Methods: The study comprised 144 women diagnosed with GDM and 52 normal control pregnancy (NC). Venous fasting serum samples were collected during the second trimester. The serum FFA levels were detected by liquid chromatography-mass spectrometry (LC-MS). The primary outcome consisted of serious maternal and neonatal adverse events ( hypertensive disorder complicating pregnancy (HDCP) , emergency cesarean section, large for gestational age (LGA) , small for gestational age (SGA) , macrosomia, low birth weight (LBW) , preterm birth, and stillbirth). The association of metrics with outcomes was assessed, and receiver operating characteristic (ROC) curve analysis was employed to evaluate clinical utility. Results: Differences in fatty acid profiles were observed between GDM patients and controls. Stearic acid (C18:0) levels differed between the normal pregnancy outcome (NPO) and APO groups, potentially correlating with fetal sex. Logistic regression models indicated that moderate and high levels of C18:0 were negatively associated with APO relative to the NPO group. ROC analysis demonstrated that C18:0 had a certain predictive ability for APO, and predictive efficiency was enhanced when combined with general clinical data. Conclusion: The level of C18:0 was associated with the occurrence of APO in pregnant women with GDM and exhibited a certain predictive value. When C18:0 was combined with general clinical data, the predictive power for APO was improved.